General self-efficacy and source memory : a preliminary investigation of causation. - Siew, Choo Ting. (2012)
The purpose of this study was to explore the relation between source monitoring abilities, suggestibility and general self-efficacy. Forty undergraduates participated in a Boggle game against a pseudo opponent, in which their level of general self-efficacy was manipulated. Following the manipulation, participants then completed a source monitoring test. Results showed that source monitoring abilities did not differ between self-efficacy groups. However, difficulty of the opponent had an effect on participant‘s source monitoring abilities. Participants were then given misinformation regarding the sources by presentation of pseudo answers from their opponents. Results showed that suggestibility was also unaffected by general self-efficacy, but was affected by the difficulty of the opponent. Furthermore, participants manipulated to have higher general self-efficacy beliefs did not demonstrate greater confidence in their responses. However, participants in the paradigm displayed good ability in predicting their own accuracy on source monitoring tests.